Investigating task design aspects that stimulate curiosity, creativity, and reflection among grade six learners in an after-school mathematics club - Baart, Noluntu Via (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.